Gender equity and inclusion in Ghana; good intentions, uneven progress. (2nd January 2020) - Ayentimi, Desmond Tutu; Abadi, Hossein Ali; Adjei, Bernice; Burgess, John
ABSTRACT: The purpose of this paper is to evaluate gender, equality and inclusion within Ghana through the examination of legislations, policies and programmes. The paper evaluates what governments, international organisations and civil society groups have been marshalling towards addressing issues around the world of work, with particular focus on gender diversity, equality and inclusion in Ghana. The paper highlights the fact that gender objectives have gained recognition and public policy momentum, yet gender segregation, wage inequality and low participation rates for females in tertiary education and the professional workforce do not match the rhetoric of the policy pronouncements.